2018
DOI: 10.1158/1078-0432.ccr-17-1594
|View full text |Cite
|
Sign up to set email alerts
|

HSF1 Is Essential for Myeloma Cell Survival and A Promising Therapeutic Target

Abstract: Myeloma is a plasma cell malignancy characterized by the overproduction of immunoglobulin, and is therefore susceptible to therapies targeting protein homeostasis. We hypothesized that heat shock factor 1 (HSF1) was an attractive therapeutic target for myeloma due to its direct regulation of transcriptional programs implicated in both protein homeostasis and the oncogenic phenotype. Here, we interrogate HSF1 as a therapeutic target in myeloma using bioinformatic, genetic, and pharmacologic means. To assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 47 publications
5
34
0
Order By: Relevance
“…The fact that the MM.1S and MM.1R lines responded differently to MEK inhibition was an interesting finding as these are both derived from the MM.1 line, with the key difference being the latter lacking a GR, raising the potential for convergence between GR-mediated and RAS-MAPK signalling [26]. Therefore, we confirmed target engagement of both trametinib and dexamethasone using known pharmacodynamic biomarkers phospho-ERK1/2 [18] and FKBP5 [27] in MM.1S and MM.1R cells (Fig. 1c).…”
Section: Ras-mutant Myeloma Cell Lines Demonstrate Differential Sensisupporting
confidence: 52%
“…The fact that the MM.1S and MM.1R lines responded differently to MEK inhibition was an interesting finding as these are both derived from the MM.1 line, with the key difference being the latter lacking a GR, raising the potential for convergence between GR-mediated and RAS-MAPK signalling [26]. Therefore, we confirmed target engagement of both trametinib and dexamethasone using known pharmacodynamic biomarkers phospho-ERK1/2 [18] and FKBP5 [27] in MM.1S and MM.1R cells (Fig. 1c).…”
Section: Ras-mutant Myeloma Cell Lines Demonstrate Differential Sensisupporting
confidence: 52%
“…Furthermore, because HSP47 acts as a universal molecular chaperone for collagen, they proposed that inhibition of HSP47 could be a good candidate for controlling tissue fibrosis [52]. Conversely, several studies have showed an unexpected pro-oncogenic role of HSF1 [53, 54]. HSF1 remains latent in primary cells without stress, it becomes constitutively activated within malignant cells, rendering them addicted to HSF1 for their growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a lot of efforts have been made to develop inhibitors that could target both chaperones. To this aim, CCT251236 or KRIBB11, novel Heat Shock Factor 1 (HSF1) inhibitors, have shown cytotoxic effects in MM cells, via induction of UPR, with altered EIF2α phosphorylation, CHOP expression and a reduction in protein synthesis (78). Thus, chaperone targeting seems a promising approach for the treatment of MM.…”
Section: Targeting Mm-associated Anomalies In Molecules Involved In Tmentioning
confidence: 99%